Experiences of Diabetic Vulnerability Community in Health Protocol Compliance During the COVID-19 Pandemic - Alik Septian Mubarrok; Fitri Firranda Nurmalisyah (Babali Nursing Research, 2022)
Introduction: Compliance with health protocols in the community including the Diabetic Vulnerable Group is one step to prevent the transmission of COVID-19, but the decline in physical and psychosocial functions in the Diabetic Vulnerable Group can be an obstacle for the Diabetic Vulnerable Group in implementing health protocols. This study aims to explore the experience of the Diabetic Vulnerable Group in implementing health protocols during the COVID-19 pandemic. Methods: A qualitative research conducted in Jatiduwur, Jombang, East Java, by conducting In-Depth interviews on 10 Diabetic Vulnerable Groups as main informants and 2 supporting informants, Ponkesdes Nurses and Midwives. Results: There are 3 themes that can be concluded from this study, namely 1) Description of various experiences of the Diabetic Vulnerable Group in implementing health protocols (uncomfortable using masks, uncomfortable washing hands frequently, keeping distance is not a problem and often forgetting to apply health protocols); 2) Motivation of the Diabetic Vulnerable Group in implementing health protocols (for health, so that the pandemic will pass quickly and government regulations compliance) and 3) Support for the Diabetic Vulnerable Group in implementing health protocols (family support and social support). Conclusion: The various experiences felt by the Diabetic Vulnerable Group in implementing health protocols are an illustration of a decrease in physical and psychosocial functions but the Diabetic Vulnerable Group remains motivated because they follow government recommendations and there is good support from families, from fellow Diabetic Vulnerable Groups and from other parties Village government.